Evaluation of two estrus synchronization protocols in dairy cattle at North Shoa zone Ethiopia - Chanyalew, Yeshimebet; Zewde, Tesfaye; Gatew, Hulunim; Girma, Lina; Kassa, Getachew; Demis, Chekol; Bihon, Amare; Tsegaye, Yeshak (ANIMAL PRODUCTION, 2017)
This study was initiated to change the hesitation of the farmer on the effectiveness of estrus synchronization under their (Ethiopian small holder) livestock management system using two synchronization protocols. Non-pregnant animals with normal reproductive tract and that fulfilled the preconditions for estrus synchronization were considered for treatment & assigned into two synchronization protocols (single PGF2Î± injection; and double PGF2Î± injection). Among 94 (27 heifer and 67 cows) synchronized cows using one and two injections of PGF2Î± protocols 26 heifers and 63 cows (89/94.7%) were exhibited estrus by visual observation and rectal palpation the remaining 5 (5.3%) did not illustrate heat. The overall pregnancy was 59.6 % with overall birth 94.3 %. High pregnancy was obtained in the double injection of PGF2Î± treatment group (63.1 %) than animals treated with one shot protocol 55.8 % there were statistically significant difference between treatments (p<0.05). Higher pregnancy was obtained from cross breed animals than local breeds. More over most of the animals come to estrus greater than 96 hrs. There was also significant difference between technicians on detecting the CL and conception. The estrus response, conception rate, pregnancy rate and calving rate was higher in both protocols so producers or farmers can use either the two protocols to achieve remarkable result but tight follow-ups and more resources are need to be exploited at farmer level.